Experience and enlightenment: "Customer-oriented" nine-stage major gifts management model of world-class U.S. universities - Chenghua Lin; Yanjie Xie; Ruixue Xu (Universidad de Deusto, 2019)
Since the 1990s, "customer orientation" marketing has been widely applied to major gifts management of world-class U.S. universities, forming a donor-centered model for major gifts management. It focuses on donor demands management, relationship cultivation and value creation, which has a major effect on university fundraising and development. Through literature review and case study of the University of Pittsburgh, this study analyzes the major gifts management model of world-class U.S. universities in terms of theory, structure, operation model, and development characteristics. The findings show that there are two important characteristics of the organizational structure of major gifts management in the United States: one is the donation market segmentation and the donor classification management; the other is the refinement of donation management functions. And this paper proposes a nine-stage major gifts management model of world-class U.S. universities, which contains "Definition-Identification- Qualification-Development of Strategy-Cultivation-Solicitation-Negotiation-Acknowledgment -Stewardship." Finally, this paper summarizes the development trend of major gifts management: emphasizing donor's value creation, donor internalization and capitalization, cultivating prospective donors from national to international, moving towards integration of leading capacity building and donor orientation. Received: 08 April 2019 Accepted: 05 November 2019 Published online: 29 November 2019